Teacher's pereceptions of principals' leadership in school renewal processes - Cavanagh, Rob; MacNeill, Clinton (AARE Inc., 2005)
This paper represents one part of a symposium presented at the annual conference of the Australian Association for research in Education. This research was part of a mixed methods study that examined teachers’ perceptions of principals’ roles in influencing changes in teachers’ pedagogic practices. Although qualitative and quantitative methods were invoked sequentially at different points in the study, only the qualitative phase of the larger study is reported in this paper. Research Objectives The research question was: What are teachers’ views of principals’ behaviours in bringing about a renewal of pedagogy within the school? The contingent objective was to empirically develop a conceptual framework of the dimensions of principals’ pedagogic, renewist behaviour.